Trajetórias de pessoas com deficiência de Jerônimo Monteiro/ES: implicações dos laudos do olhar no direito à educação - Lima, Jovenildo da Cruz (2019)
The dissertation aims to reconstruct the trajectory lived by people considered to have some kind of disability in the municipality of Jerônimo Monteiro / ES - considering different historical moments - and make them dialogue with the ways the school means the process of inclusion of public students. target of special education today. It brings reflections on the implications of social diagnoses in the enjoyment of various rights, especially education. It comprises a certain corpus of knowledge that aims to help teaching units (at present) to analyze the impacts of school diagnoses (“eye reports”) on the teaching-learning processes of students with disabilities, global developmental disorders and high skills. giftedness. Dialogue with Boaventura de Sousa Santos (2006, 2007, 2008) and Lilia Ferreira Lobo (2015), as well as researchers in the field of special education. Methodologically, it is based on the assumptions of narratives and documentary research. The data collection consisted of interrelated moments: a) documentary consultation to recompose the history of the city and data related to Education and Special Education; b) survey of the subjects participating in the research through the composition of two working groups (Group 1 with people who lived with the subjects who recomposed their life trajectories, and Group 2 with teachers who work with current target audience students); c) conducting group interviews with participants in Group 1; c) application of questionnaires to the teachers of Group 2; d) organization, categorization and analysis of data. The research was conducted in the second semester of 2018 and the first of 2019, having as data collection instrument the field diary, focus group filming, interview recording and questionnaires. As a result, the study demonstrates that the trajectories of the investigated people suffered implications of social diagnoses produced from their modes of existence; whereas the difficulties encountered by society in dealing with subjects with significant differences promote exclusionary processes in a multifaceted manner; that education systems (nowadays) need to compose public policies (with emphasis on teacher education), considering that the “eye reports” produced in school collectives can promote processes of exclusion of the target public students from special education. right to learn, contrary to the Brazilian Constitution of 1988.